Exporting and the environment: a new look with micro-data - Sourafel Girma; Aoife Hanley; Felix Tintelnot (Kiel Institute for the World Economy (IfW), 2008)
Previous aggregate studies ignore additional environmental improvements caused by intra industry reallocations to high productivity/ low pollution firms. They also fail to consider potential differences in abatement efforts by exporting status. Our estimation based on UK firm level data from 1998 to 2002 shows that exporters are 7.5 percent more likely to denote their innovation as having a ?high? or ?very high? environmental effect. Our findings also show that exporters are 17.5 percent more likely, all things equal, to report that their firm's innovation cuts the cost of energy/ materials. Our results agree with our environment trade model which predicts that exporters amortize the fixed cost of environmental abatement over their wider output base
Keywords: Q55; Q56; O31; 330; Exporting; environment; innovation; heterogeneity; Exportindustrie; Umweltschutzkosten; Umwelttechnik; Innovation; Großbritannien